On-site monitoring of trace levels of free manganese in sea water via sonoelectroanalysis using a boron-doped diamond electrode - Goodwin, A; Lawrence, A; Banks, C; Wantz, F; Omanovic, D; Komorsky-Lovric, E; Compton, R (2005)
Cathodic stripping voltammetry at a boron-doped diamond electrode utilising an insonated accumulation protocol is shown to be possible for the on-site trace detection of free manganese in seawater samples. No sample pre-treatment is required with the application of ultrasound providing a sensitive and selective protocol for the analysis of manganese. The protocol is used in the evaluation of manganese in seawater samples taken near the site of a former ferromanganese factory in the town Šibenik, Croatia. © 2004 Elsevier B.V. All rights reserved.